Assessment of antigenic supplementation of bovine purified protein derivative for diagnosis of subclinical infection with Mycobacterium bovis in cattle. (July 2017) - Alvarez, A.H.; Gutiérrez-Ortega, A.; Gómez-Entzin, V.; Pérez-Mayorga, G.; Naranjo-Bastién, J.; González-Martínez, V.; Milián-Suazo, F.; Martínez-Velázquez, M.; Herrera-Rodríguez, S.; Hinojoza-Loza, E.
Abstract: Bovine tuberculosis (bTB) is usually diagnosed in vivo and ex vivo on the basis of delayed hypersensitivity reactions with a complex pool of antigens named bovine tuberculin (PPDB). The IFN-γ release assay (IGRA) for bTB is a blood-based assay that improves detection of infected cattle at early stages that escape skin testing. Improvements to IFN-γ testing with specific proteins have been performed to increase sensitivity. DosR regulon-related antigens are well known mycobacterial proteins expressed during the non-replicative phases of infection, this has been useful to improve the diagnosis of subclinical forms of TB in suspected individuals. Transcripts of DosR genes mb2054c, mb2057c, and mb2660c have been identified by our group in lymph nodes of IFN-γ test negative cattle. This led us to hypothesize that DosR-related proteins may potentiate the IFN-γ response to PPDB in animals with a false negative IFN-γ test, making evident subclinical infection. Three hundred animals were evaluated by means of IGRA and post-mortem microbiological analysis of tissue samples to validate M. bovis infection. We found that 176 out of 300 animals showed an overall increased OD in complemented IGRA with two purified protein cocktails in comparison to PPDB alone, and were scrutinized for a subclinical infection; thirty percent when PPDB was supplemented with a cocktail of four DosR antigens, and 70% when PPDB was supplemented with a cocktail of six antigens (four DosR and two RD1 antigens). Forty five animals showed a substantial IFN-γ overproduction but remained negative, and 40 animals changed the result to a positive test. Only 18 out of 176 IFN-γ high producing animals were also positive to M. bovis isolation. Fifty seven animals with no visible lesions at slaughter and with a negative IGRA test result contained M. bovis DNA in tissue samples. In conclusion, Mb1762c, Mb2054c, Mb2057c, and Mb2660c have the potential to increase sensitivity of the IFN-γ in vitro test for bTB diagnosis when supplemented to PPDB. Highlights: Complete DosR proteins Mb1762c, Mb2054c, Mb2057c, and Mb2660c augment sensitivity of IGRA test against bovine TB. Antigens Mb1762c, Mb2054c, Mb2057c, and Mb2660c of M. bovis have good propensities to bind MHC-class II molecules. Complementation of IGRA test with DosR antigens may potentiate PPDB for M. bovis subclinical infection in cattle. Some IGRA -ve animals may contain bacterial DNA and non-cultivable bacteria. Supplemented IGRA test allow detection of infected animals where probably M. bovis is not actively replicating.